Where are parking policies most popular? Empirical findings about the influence of the residential neighbourhood and car parking characteristics on public acceptability - Baumgartner, Annabell; Lanzendorf, Martin (Transport policy, 2025)
Parking policies are a key factor in reducing car usage and improving liveability in urban neighbourhoods, as they link transport and land use. However, policymakers face the challenge of designing parking policies that effectively address local car parking issues while ensuring acceptability within the same neighbourhood. Our empirical analysis aims to develop a typology of different parking policies based on residents’ acceptability. Furthermore, we investigate the influence of spatial differences on the acceptability of parking policies, focusing on the residential neighbourhood and car parking characteristics. We derive our findings from a quantitative household survey (N = 1186) we conducted in eight neighbourhoods in the two German cities of Darmstadt and Frankfurt am Main. Applying principal component analysis (PCA) to 31 initial parking policies, we identify six policy types: (1) parking restrictions and enforcement, (2) conversion of parking space for liveability, (3) conversion of parking space for mobility services, (4) parking space conversion accompanied by additional measures, (5) additional neighbourhood garages and (6) limited parking for SUVs. Our results show that push measures are both among the most accepted and rejected policies, with restrictions for SUVs being generally more popular than those for regular cars. Moreover, we find that the acceptability of the conversion of parking spaces depends on the proposed alternative land use and accompanying additional measures. Despite some disparities, residents are more supportive of parking space conversions for liveability (e.g. greenery) than for alternative mobility services (e.g. car sharing stations). Our results also highlight the important role of the neighbourhood level when setting parking policies. Multivariate analyses indicate that the residential neighbourhood and car parking characteristics, such as the usual parking location, duration and distance from home, influence the acceptability of parking policies. Policymakers might, therefore, consider the local parking situation to be changed in a neighbourhood, the specific target groups to be addressed by a policy and the benefits for residents to be promoted by a transformation of on-street car parking. •A majority of residents support push policies that target SUVs only.•Converting parking space for liveability is more popular than for mobility services.•Residents are more supportive of parking policies in dense urban neighbourhoods.•A longer parking duration increases the acceptability of parking policies.